ON THE ORIENTABILITY OF THE GRASSMANN MANIFOLDS - Trenčevski, Kostadin (Matematichki Bilten, 1997)
In [3] it is proved that the Grassmann manifold \(G_{p,q}(R)\) is orientable if and only if \(p+q\) is even number. In this paper it is given alternative proof of this statement.